Fabrication of Enzyme Nanoparticles-based Nanosensor for Detection of Nitrate Content in Drinking Water - Sharma, Dr. Minakshi (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: An advanced amperometric biosensor was designed based on immobilization of nitrate reductase nanoparticles (NaRNPs) on gold (Au) electrode. Materials and Methods: NaRNPs were prepared by chemical desolvation and glutaraldehyde cross-linking method to form nanoaggregate and characterized by transmission electron microscopy and ultraviolet–visible spectroscopy. NaRNPs/Au electrode was evaluated by scanning electron microscopy and Fourier-transform infrared spectroscopy. Results and Discussion: A linear relationship was observed between biosensor response, i.e., current milliampere and nitrate concentration in the range of 0.1 μM–200 μM showing lower detection limit of 0.14 mM with a response time of 2 s on 0.2 V–1.2 V at scan rate 50 mV/s under optimum pH 7.0 and temperature 35°C. Conclusion: A lower value of Km (384.61 μM) with Vmax (1219.512 μmol (min mg protein)-1), storage stability of 90 days, and low detection limit 0.14 μM nitrate content in drinking water samples was obtained.